Hypo-osmotic swelling test modification to enhance cell membrane integrity evaluation in cryopreserved bull semen - Baiee, Falah Hasan Ali; Haron, Abd Wahid; Yusoff, Rosnina; Omar, Mohamed Ariff; Degu, Nurhusien Yimer; Ghareeb, Salman Hammadi; Abdelbagi, Tarig Abdelrouf Ahmedeltayeb; Mada, Khumran Armiya'u (Universiti Putra Malaysia Press, 2017)
The objective of this study was to enhance the hypo-osmotic swelling test evaluation when it reads under light microscope using 5% formaldehyde-fixed sperm solution buffer (FSSB). Twenty four ejaculates were collected from six crossbred bulls using electro-ejaculator (EE). Tris-egg yolk extender was used to cryopreserve the semen. Concentration, volume, motility, morphology and viability rates of fresh semen were evaluated and samples were cryopreserved in liquid nitrogen. After two weeks of liquid nitrogen treatment (freezing), the motility, morphology and viability rate of the semen were evaluated. In order to carry out a hypo-osmotic swelling test, post-thaw semen was divided into four aliquots based on period of incubation (30 or 60 minutes) adding FSSB to half the samples. The components of FSSB were 5% formaldehyde and 1% eosin-nigrosin stain in PBS. Results showed that F (61.48 ±0.89%) resulted in higher percentage (P<0.05) of total membrane intact compared with F 60 30 (54.40 ±1.34%) and N 30 (53.96±1.17%), but did not differ (P>0.05) with N60 (60.90±0.70%). In conclusion, adding 10 µl of FSSB after 60 minute of incubation with hypo-osmotic swelling solution (HOSS) will enhance evaluation of the hypo-osmotic swelling test (HOST) under light microscope.